Analysis of the Manpower Supply Strategy at PT Bank Pembangunan Daerah Jawa Barat and Banten, Tbk with the SWOT Analysis Method - Ranthy Pancasasti; Ujang Aep Saefulloh; Yugi Adhari Nugraha (IJHCM (International Journal of Human Capital Management), 2021)
The purpose of this study was to analyze the provision of human resources at PT Bank Pembangunan Daerah Jawa Barat and Banten, Tbk. Where the provision of human resources is very important for the sustainability and development of the company. It is important for companies to be able to determine strategies and steps that must be taken to determine effective strategies in providing human resources that are used to analyze SWOT. Data analysis uses SWOT matrix analysis by considering strengths, weaknesses, opportunities, and threats. The results of the study indicate that when the provision of human resources is differentiated based on external and internal factors, it is found that the company can choose the provision of human resources both internally and externally according to the company's needs